On M-polynomial and some topological indices of Favipiravir (T – 705) and Ribavirin. (3rd October 2021) - Bharali, Ankur; Pegu, Aditya; Agarwal, Priyanka; Chamua, Monjit
Abstract: The coronavirus disease (COVID-19) is upsetting human well-being and the economy around the globe. Scientists have been trying some antiviral drugs to control the disease and transmission of the 2019-nCoV in vitro. Two of these compounds are Favipiravir ( T –705) and Ribavirin. Topological index also known as connectivity index, is a molecular descriptor which is calculated based on the molecular graph of a chemical compound. Topological indices are used to predict different biological and physicochemical properties of chemical compounds. In this article, various significant topological degree-based indices and the M-polynomials are investigated for the Favipiravir( T –705) and Ribavirin. The results obtained may aid in the designing of new medicine for the treatment and prevention of COVID-19 and other diseases.